Bigger change faster: Integrated development, health and environment actions for a sustainable future - Goldstein, J.; Tallis, H.; Linou, N.; Small, R.; Ringler, Claudia; Huikuri, S.; Kreis, Katharine; Olander, L.; Jacobs, C.; Kelso, M.; Mason, S.; Zobrist, S. (International Food Policy Research Institute, 2019)
The United Nations 2030 Agenda for Sustainable Development (2030 Agenda) sets forth an ambitious vision for all countries to advance the well-being of people and the planet (UNGA 2015). Oriented around 17 Sustainable Development Goals (SDGs) and a pledge to leave no one behind, the 2030 Agenda provides the most formal recognition to date of the interwoven challenges across development, health, and the environment that must be overcome to realise a better world for all. In parallel, efforts have increased to establish an evidence base on the inextricable links between human health and the natural systems which underpin it (Whitmee et al. 2015, WHO and CBD 2015). Today, environmental risks are responsible for nearly one quarter of all premature and preventable deaths globally (Prüss-Ustün et al. 2016). Climate change in particular is recognised as one of the greatest threats to human health, poverty alleviation, and broader human development in the 21st century (Rigaud et al. 2018, Watts et al. 2018). Furthermore, degraded environments and poor health are root causes of many other development challenges, from food insecurity to poverty and inequality, that limit society’s ability to deliver effective solutions for people and the planet. Delivering on the transformative vision of the 2030 Agenda and related global commitments, including the Paris Agreement, will require an unprecedented level of political leadership, knowledge, collaboration, investment, and action across local, national, and global scales. The SDGs compel actors tackling development, health, or environmental issues to work together more effectively for greater impact. SDG 17 specifically focuses on strengthening the means of implementation and revitalising the global partnership for sustainable development. With a decade to go until 2030, the time to act is now. Decisions taken in the next few years will have a major impact on society’s ability to achieve the pace and scale of change needed. Yet solutions are still largely designed and implemented in isolation, without a broader view of connections across sectors1 . Approaching and tackling interventions in siloes too often leads to inefficient use of scarce resources. Of equal importance is that siloed interventions can lead to positive outcomes for one sector at the expense of other sectors’ goals. Limitations like these undermine the progress needed to achieve the SDGs and the pledge to leave no one behind.